The girl who chased away sorrow : the diary of Sarah Nita, a Navajo girl - Turner, Ann Warren (Dear America, 1999)
Sarah Nita uses her education at the white man's school to write down her grandmother's account of the Long Walk of 1864, during which the Navajo people were driven off their land and forced by soldiers to take refuge in Fort Sumner.